Mechanical behavior of high strength S690-QT steel welded sections with various heat input energy. (15th November 2018) - Liu, Xiao; Chung, Kwok-Fai; Ho, Ho-Cheung; Xiao, Meng; Hou, Zhao-Xin; Nethercot, David A.
Highlights: S690-QT steels suffer reduction in mechanical properties after welding. Tensile tests on welded sections with different heat input energy are conducted. Typical heat input energy of welded sections ranges from 1.0 to 5.0 kJ/mm. Almost all coupons of the welded sections fracture within the HAZs. For 1.0 kJ/mm, there is almost no reduction in the mechanical properties. For 5.0 kJ/mm, only 70% of the yield strength of the base plates is attained. Abstract: Over the past two decades, there were a number of experimental investigations into mechanical properties as well as structural behaviour of high strength S690-QT steel welded sections. It is evident now that, similar to structural aluminium, these welded sections will suffer from a significant reduction in their mechanical properties, i.e. both yield and tensile strengths as well as ductility, due to change in microstructures if welding is not properly controlled. Owing to a lack of detailed understanding on effects of various welding procedures and parameters onto the mechanical properties of these steel welded sections, many design and construction engineers have serious concerns on adopting these S690-QT steel materials in buildings and bridges. This project aims to investigate and quantify effects of various line heat input energy onto the mechanical properties of the S690-QT steel welded sections through a series of carefully planned and executed standard tensile tests. A total of 12 standard tensile tests on cylindrical coupons of welded sections were conducted, and full range deformation characteristics of these coupons were obtained through use of strain gauges and measurements on high resolution digital images. Both welding methods, namely, GMAW and SAW, were employed to prepare full penetration butt-welded sections with various line heat input energy. It should be noted that GMAW was performed with a robotic welding system while SAW was performed with an automated welding machine to attain high quality welding consistently. Additional standard tensile tests on 3 reference coupons machined from the base plates, and another 3 reference coupons machined from the weld metal were also conducted to provide basic material properties for direct comparison. It was shown that in almost all coupons of the welded sections tested in the present study, fracture occurred within the heat affected zones of the welded sections without any failure in neither the weld metal nor the base plates. For welded sections prepared with a line heat input energy equal to 1.0 kJ/mm, there was almost no reduction in the mechanical properties of the welded sections. However, for those welded sections prepared with a line heat input energy equal to 5.0 kJ/mm, only 70% of the yield strength of the base plates was attained. Consequently, the effects of welding onto the mechanical properties of the S690-QT steel welded sections have been successfully quantified, and the information is readily adopted in assessing their mechanical behaviour according to various line heat input energy employed during welding.